Pengaruh Program Kartu Prakerja terhadap Penyerapan Tenaga Kerja Indonesia pada Masa Pandemi Covid - 19 - Bahruddin Zaki; Tri Kartika Pertiwi (Jurnal Ilmiah Dikdaya, 2023)
The COVID-19 pandemic has intensified in 2020 so that many Indonesian workers have been laid off and unemployed. In order to increase the rate of employment during the pandemic and reduce the open unemployment rate, the Indonesian government has created a pre-employment card program that provides opportunities for job seekers to obtain job training and skills that are relevant to industry needs. This study was made with the aim of knowing the impact of the pre-employment card program on the absorption level of Indonesian workers during the COVID-19 pandemic. The study used samples from the entire population consisting of regencies and cities in Indonesia, with secondary data from employment data and information centers. This study uses a quantitative approach, using simple regression analysis to test and validate the hypothesis. The results showed that there was a significant positive effect between the provision of the pre-employment card program and the level of employment.